The Assessment and Management of Childhood Masturbation: An Analysis of 90 Cases - Güleç, Ayten; Öztürk, Selcan; Acer, Hamit; Canpolat, Mehmet; Gümüş, Hakan; Per, Hüseyin (Neuropediatrics, 2024)
Aim The child's self-stimulating pleasure behavior is defined as childhood masturbation (CM). Diagnosis of CM is mainly based on behavior and analysis of video recordings. This study aims to investigate etiological factors, movement patterns, and treatment options.Medical records and video recordings of CM in our clinic between 2015 and 2020 were retrospectively reviewed.Results Ninety patients aged 8 months to 9 years were included in our study. The male-to-female ratio was 23/67. The mean age at onset of masturbation (mean ± standard deviation) was 21.42 ± 18.44 (6–107) months. Note that 27.7% (32) of the patients were taking antiepileptic drugs before admission.Eight of the 90 patients had abnormal electroencephalograms. The time of onset of CM was related to cessation of breast milk in 24.4%, separation from the mother in 43.3%, new siblings in 16.6%, initiation of toilet training in 7.7%, and parental divorce in 6.6%. Behavioral therapy was sufficient in 71.1%. Hydroxyzine hydrochloride in 19 (21.1%) and risperidone in 9 (10%) were given in the remaining cases. Overall, 23/28 of the cases receiving medication improved during follow-up.Conclusion Physicians may have difficulty identifying repetitive movements in CM. Misdiagnosis or delayed diagnosis may lead to unnecessary use of antiepileptic drugs, delayed initiation of treatment, and prolonged treatment duration. Video recordings are important in the differential diagnosis of CM. CM may have psychosocial causes and can often be effectively treated with behavioral therapy. Pharmacological treatment (hydroxyzine hydrochloride and risperidone) may be considered in cases that do not respond to behavioral treatment.
Keywords: masturbation; nonepileptic seizures; psychomotor disorders; behavioral therapy